a)-3 + 2x - 6 = 3 - 40
b)2 (21+4) - 5(x + 3) = 2
c) (4 - x) - (2x + 3) + (x – 4) = - (2x - 3) - (x+7)
d)0,7% - 3+1,1% = -2,12 +0,6
5 1
e)x/3 -⅚= 1/12 - x/2
plis na już mam sprawdzian ​


Odpowiedź :

Odpowiedź:

a) -3+2x-6=3-40                b) 2*(21+4)-5*(x+3)=2

-9+2x=-37                              42+8-5x+15=2

2x=37+9                                 65-5x=2

2x=46/ podzielić 2                 5x=2-65

x=23                                         5x=-63/podzielic 5

                                                  x=12 3/10

Szczegółowe wyjaśnienie:

umiem tylko tyle